ChemInform Abstract: Selective Synthesis of 4‐(Sulfonyl)‐methyl‐1H‐pyrazoles and (E)‐4, 5‐Dihydro‐1H‐pyrazoles from N‐Allenic Sulfonylhydrazones. Issue 44 (4th November 2014) - Zhu, Yu; Hong, Jun‐Jie; Zhou, Yun‐Bin; Xiao, Yu‐Wei; Lin, Min; Zhan, Zhuang‐Ping
Abstract A key feature of the title reaction is that the migration of the sulfonyl groups to different positions can be controlled by changing the Lewis acids.